Customs Modernization Handbook. - Wulf, Luc de, 1942-; Sokol, José B. (Trade and development series., 2005)
"The Customs Modernization Handbook draws on lessons from a sample of successful customs reform initiatives and on the experiences of the Bank, to present the main elements of a customs modernization strategy. It provides operational guidelines to deal with issues such as customs valuation, rules of origin, duty relief and exemptions, transit and security issues, and use of information technology. It also provides guidance on such issues as legal framework, human resource management, the fight against corruption, and management autonomy."--Jacket.